Divergent responses of vegetation cover in Southwestern US ecosystems to dry and wet years at different elevations. (24th November 2016) - Herrmann, Stefanie M; Didan, Kamel; Barreto-Munoz, Armando; Crimmins, Michael A
Abstract: In the semiarid Southwestern United States, prolonged drought conditions since the early 2000s have resulted in widespread declines of the vegetation productivity in this water-constrained ecosystem, as revealed by analyses of the Normalized Difference Vegetation Index (NDVI). However, the spatial pattern of the NDVI response to dry years is not uniform: a divergent response of NDVI to precipitation is observed between the low-lying desert and the high montane forests at elevations above 2, 500 meter. We analyzed relationships between 15 years of Moderate Resolution Imaging Spectroradiometer (MODIS) NDVI and gridded climate data (PRISM) along elevation gradients at scales from regional to local. Our elevation-explicit analysis captures the transition from water-limited to temperature-limited ecosystems, with a sign-reversal in the correlation coefficient between precipitation and NDVI observed at about 2, 500-3, 000m altitude. We suggest warmer temperatures and less snow cover associated with drier years as explanations for high elevation gains in vegetation productivity during dry years.